Immediate and long-term effects of psychological stress during adolescence in cardiovascular function: comparison of homotypic vs heterotypic stress regimens - Duarte, Josiane de Oliveira [UNESP]; Planeta, Cleopatra da Silva [UNESP]; Crestani, Carlos Cesar [UNESP] (Wiley, 2015)
Adolescence has been proposed as an ontogenic period of vulnerability to stress. Nevertheless, the impact of stressful events during adolescence in cardiovascular activity is poorly understood. Therefore, the purpose of this study was to investigate the immediate and long-lasting effects of exposure to stressful events during adolescence in cardiovascular function of rats. To this end, we compared the impact of 10-days exposure to two chronic stress protocols: the repeated restraint stress (RRS, homotypic) and chronic variable stress (CVS, heterotypic). Independent groups of animals were tested 24 h (immediate) or three weeks (long-lasting) following completion of stress period. Exposure to CVS, but not RRS, during adolescence increased basal HR values without affecting arterial pressure, which was followed by augmented power of oscillatory component at low frequency (sympathetic-related) of the pulse interval (PI). RRS enhanced variance of the PI with an increase in the power of both low and high (parasympathetic-related) frequency components. RRS also increased the baroreflex gain. Neither RRS nor CVS affected systolic arterial pressure variability. The RRS-evoked changes in PI variability were long-lasting and persisted into adulthood while all alterations evoked by the CVS were reversed in adulthood. These findings indicate a stress type-specific influence in immediate and long-term effects of stress during adolescence in cardiovascular function. While immediate changes in cardiovascular function were mainly observed following CVS, long-lasting autonomic consequences in adulthood were observed only in animals exposed to RRS during adolescence.
Keywords: Unpredictable stress; Chronic variable stress; Restraint stress; Autonomic; Baroreflex; Ontogeny